'Indianization' of Indonesia in an Historical Sketch - Taufiq Rahman (UIN Sunan Gunung Djati Bandung, 2013)
This Article gives some remarks on the history of Indianization in Indonesian archipelago in me remote history. The illustration includes bow this process of Indian influences grew and developed, both in the palaces and the societies. Given this remark the writer comes to the projection on how natural this process was. By reflecting the past the writer is sure that the plurality of religions and cultures in Indonesia is a kind of destiny to be faced peacefully in order to keep the harmony in the nation's social life.